Effects of Activating Mutations on EGFR Cellular Protein Turnover and Amino Acid Recycling Determined Using SILAC Mass Spectrometry - Michael J. Greig; Sherry Niessen; Scott L. Weinrich; Jun Li Feng; Manli Shi; Ted O. Johnson (International Journal of Cell Biology)
Rapid mutations of proteins that are targeted in cancer therapy often lead to drug resistance. Often, the mutation directly affects a drug’s binding site, effectively blocking binding of the drug, but these mutations can have other effects such as changing the protein turnover half-life. Utilizing SILAC MS, we measured the cellular turnover rates of an important non-small cell lung cancer target, epidermal growth factor receptor (EGFR). Wild-type (WT) EGFR, EGFR with a single activating mutant (Del 746–750 or L858R), and the drug-resistant double mutant (L858R/T790M) EGFR were analyzed. In non-small cell lung cancer cell lines, EGFR turnover rates ranged from 28 hours in A431 cells (WT) to 7.5 hours in the PC-9 cells (Del 746–750 mutant). The measurement of EGFR turnover rate in PC-9 cells dosed with irreversible inhibitors has additional complexity due to inhibitor effects on cell viability and results were reported as a range. Finally, essential amino acid recycling (K and R) was measured in different cell lines. The recycling was different in each cell line, but the overall inclusion of the effect of amino acid recycling on calculating EGFR turnover rates resulted in a 10–20% reduction in rates.